Detected changes of population structure within a Cryphonectria parasitica population at the site Osoj, North Macedonia, during a time-span of over two decades - Risteski, Mihajlo; Cokoski, Kristijan; Tanovski, Vladimir; Sotirovski, Kiril ("Hans Em" Faculty for Forest Sciences, Landscape Architecture and Environmental Engineering, Skopje, 2022)
Cryphonectria parasitica is historically considered as one of the most threatening plant diseases, and affects several species of Castanea worldwide. Applicability and success of control measures for the pathogenic fungus, consequently for control of its impact on European sweet chestnut Castanea sativa is highly dependent on presence of hypovirulence on populational levels, as well as on the population structure characteristics, most prominently vc-type diversity. In this study we compared the main characteristics of isolates of C. parasitica collected on 2 occasions with a time gap of 22 years (1998 and 2020) from the same site Osoj in the Kicevo region, in North Macedonia. We analyzed culture morphology, v-c type, and presence of hypovirulence of 72 isolates collected in 1998 and 39 isolates in 2020, by standard methods in vitro. In terms of the v-c type, from the total of 72 isolates collected in 1998, 49 (68%) were EU-12, 22 (30,55%) were EU-2 and 1 (1,38%) was EU-1. Of the 39 isolates collected in 2020, 32 (82%) were EU-12, 7 (18%) were EU-2, and no other vc types were detected, including EU-1. In 1998, 7 (13%) out of 54 assessed isolates were designated as hypovirulent, while in 2020 the proportion of hypovirulent isolates was much increased (33.33%), i.e. 13 of the total of 39. For the two-decade time frame, v-c type EU-12 remained dominant, with an additional increment of its prevalence on the populational level. From a practical point of view, it is more important that prevalence of hypovirulence was increased by over two-fold (x 2.57). This is likely the most important reason for difficulty during collection of viable samples, ultimately leading to a much lesser number of samples collected in 2020. As a conclusion, the C. parasitica population in Osoj has not only not diversified, but the most dominant vc type has become even more established with time. The relatively high proportion of hypovirulent isolates and the large increment detected in just over two decades timeframe, is interesting to further investigate in relation to overall health status of the chestnut population in Osoj
Keywords: chestnut blight; v-c type; hypovirulence